The Effect of Vine Spacing on the Vegetative and Reproductive Performance of Vitis vinif era L. ( cv. Pinot noir) - Archer, E.; Strauss, H.C. (South African Journal of Enology and Viticulture, 2017)
Data concerning growth, yield, grape composition and wine quality are presented for five years. Closer spacing reduced cane mass and yield per vine but increased them per hectare. Less dense canopies as well as a larger leaf area: fruit mass ratio with more closely spaced vines au~mented grafe and wine quality. Given the specific circumstances of this trial, a vine spacing resulting in between 1,0 m and 2,0 m soil surface per vine proved to be optimum for Pinot noir.